2013
DOI: 10.1539/joh.13-0097-fs
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure and Thoracic Malignancies, Is There a Relationship ?

Abstract: and 300 healthy controls were enrolled in this casecontrol study. Life-long occupational history, gender, age, exposure to asbestos, comorbidities, and smoking status were collected. Results: The mean age of the 300 lung cancer cases was 60.3 ± 9.9 year (91.7% male and 8.3% female), and the mean age of healthy control group was 60.4 ± 10.5 year (95.0% male and 5.0% female). The most frequent histological types were squamous (172, 57.3%), adeno (69, 23.1%), and small cell (37, 12.3%). There was an increased ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…They identified the increased risk of lung cancer among agriculture workers (OR = 1.89, 95% Cl = 1.17−2.98) and workers exposed to inorganic dust (ceramic and pottery workers, construction, and mining) (OR = 1.81, 95% Cl = 1.0−3.25) compared to office workers. They also discovered that the elevated risk for agriculture workers was associated with pesticide use [29]. The odds ratio in our study was slightly higher than in the Baser study but comparable with a cohort study by Alavanja et al [30].…”
Section: Discussionsupporting
confidence: 87%
“…They identified the increased risk of lung cancer among agriculture workers (OR = 1.89, 95% Cl = 1.17−2.98) and workers exposed to inorganic dust (ceramic and pottery workers, construction, and mining) (OR = 1.81, 95% Cl = 1.0−3.25) compared to office workers. They also discovered that the elevated risk for agriculture workers was associated with pesticide use [29]. The odds ratio in our study was slightly higher than in the Baser study but comparable with a cohort study by Alavanja et al [30].…”
Section: Discussionsupporting
confidence: 87%
“…In a previous study from Indonesia, an elevated OR of 3.6 (95% CI: 1.2 to 10.4) was reported among farmers (both sexes) 28. Another study carried out in Turkey observed an increased risk of lung cancer among workers in agriculture with OR of 1.9 (95% CI: 1.0 to 3.2) 34. A study among Italian female farmers, also reported an elevated OR of 1.7 (95% CI: 0.7 to 4.4) for lung cancer 35.…”
Section: Discussionmentioning
confidence: 89%
“… 28 Another study carried out in Turkey observed an increased risk of lung cancer among workers in agriculture with OR of 1.9 (95% CI: 1.0 to 3.2). 34 A study among Italian female farmers, also reported an elevated OR of 1.7 (95% CI: 0.7 to 4.4) for lung cancer. 35 The female farmers in Iran mostly live in rural areas, who likely carry out other tasks in addition to farming, for example, baking and cooking, which raise the concerns about exposure to combustion of biomass fuels.…”
Section: Discussionmentioning
confidence: 95%